Generation of three human erythroblast-derived iPSC lines (UBTi002-A, UBTi002-B, and UBTi002-C) - Martina Auer; Hannah Sophie Klampfl; Peter Schlenke; Isabel Dorn (Stem Cell Research, 2025)
We reprogrammed human hematopoietic stem/progenitor cell (HSPC)-derived erythroblasts obtained from a healthy male donor. CD34+ HSPCs were differentiated ex-vivo into erythroid precursor cells and were then nucleofected with four episomal plasmids expressing SOX2, OCT3/4, KLF4, LIN28, L-MYC, and TP53-shRNA. The resulting iPSC lines displayed a normal karyotype. Pluripotency was confirmed through the expression of markers for undifferentiated human pluripotent stem cells (hPSC) and in vitro differentiation into tissues representing endoderm, mesoderm, and ectoderm. The iPSC lines UBTi002-A, UBTi002-B, and UBTi002-C are expected to serve as valuable tools for advancing research in human hematopoiesis and erythropoiesis.